Tara Leniston, Rhian Grounds Dom oswojony. Jak stworzyć bezpieczną przestrzeń dla dziecka z ASD [Tamed house. How to create a safe space for a child with ASD] Wydawnictwo Uniwersytetu Jagiellońskiego, Kraków 2020 - Świeżek, Klarysa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Tara Leniston, Rhian Grounds Dom oswojony. Jak stworzyć bezpieczną przestrzeń dla dziecka z ASD [Tamed house. How to create a safe space for a child with ASD] Wydawnictwo Uniwersytetu Jagiellońskiego, Kraków 2020